Comment penser l'erreur en régie d'art contemporain ? - Ivan Clouteau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The present article intends to engage a reflection on a theoretical frame to deal durably with the error in the registrar's and art preparator's practices in contemporary art. By taking into account on one hand the recent recognition of the activity in France and on the other hand the specificities of the contemporary art, we will examine the way in which the treatment of the error can partake in the construction of a professional model.